Graphene oxide touches blood: in vivo interactions of bio-coronated 2D materials. Issue 2 (31st October 2018) - Palmieri, V.; Perini, G.; De Spirito, M.; Papi, M.
Abstract : The impact of graphene oxide biomolecular corona on blood components. Abstract : Graphene oxide is the hot topic in biomedical and pharmaceutical research of the current decade. However, its complex interactions with human blood components complicate the transition from the promising in vitro results to clinical settings. Even though graphene oxide is made with the same atoms as our organs, tissues and cells, its bi-dimensional nature causes unique interactions with blood proteins and biological membranes and can lead to severe effects like thrombogenicity and immune cell activation. In this review, we will describe the journey of graphene oxide after injection into the bloodstream, from the initial interactions with plasma proteins to the formation of the "biomolecular corona", and biodistribution. We will consider the link between the chemical properties of graphene oxide (and its functionalized/reduced derivatives), protein binding and in vivo response. We will also summarize data on biodistribution and toxicity in view of the current knowledge of the influence of the biomolecular corona on these processes. Our aim is to shed light on the unsolved problems regarding the graphene oxide corona to build the groundwork for the future development of drug delivery technology.